INTEGRATED EVALUATION OF ANAMNESTIC DATA IN THE DIFFERENTIAL DIAGNOSIS OF TEMPOROMANDIBULAR DISORDERS AND DISEASES THAT AFFECT THEM - M.Yu. Mykhailevych; V.F. Makeev (Український стоматологічний альманах, 2021)
In modern dentistry, temporomandibular disorders (TMD) are the third most common dental disease after caries, its complications and periodontal pathology. Despite the fact that a significant amount of research has been devoted to this problem, the etiology and pathogenesis have still not fully derermined.